Time-varying state observer based twisting control of linear induction motor considering dynamic end effects with unknown load torque. (October 2019) - Zhang, Lei; Zhang, Hui; Obeid, Hussein; Laghrouche, Salah
Abstract: This paper presents a time-varying state observer based twisting control (TC) technique scheme for linear induction motor (LIM) considering dynamic end effects. With Ducan's T-model, indirect field oriented control strategy is introduced and the state space equation of LIM is obtained in ( d, q ) rotary reference frame. On this basis, LIM's model is extended to two subsystems: flux extended model and speed extended model. Twisting algorithm (TA) is applied into these two subsystems to achieve speed tracking and flux tracking with finite time convergence in the presence of disturbance and uncertainty. For the rotor flux estimation, a time-varying state observer is designed, and its stability and convergence have been proved with Lyapunov's theory. Moreover, the value of estimated LIM speed derivative is obtained via second order sliding mode observer. Furthermore, a reduced order load torque observer is designed to estimate the external load torque. The feasibility and effectiveness of proposed method has been validated by Hardware-in-the-loop (HIL) test experiment. Highlights: A robust twisting control algorithm is applied in LIM system to deal with the system uncertainty and parameter variation. A time-varying state observer is designed to improve the error convergence ratio of estimation. A second order sliding mode observer is proposed to estimate the first derivative of the LIM speed, for its advantage of finite time convergence and robustness. A reduced order observer is developed to estimate the unknown load torque, and its stability has been proved with Lyapunov's theory.